Characteristic Of Hospitalized Burn Injury Patients In Zainoel Abidin General Hospital Year 2016-2017 - Syamsul Rizal; Muhammad Jailani; Mirnasari Amirsyah; Muzammil, Emil (Lingkar Studi Bedah Plastik Foundation, 2020)
Background: The epidemiology pattern of patients with burn injury varies widely in different parts of the world. This study aimed to identify epidemiological data from hospitalized burn injury patients in Zainoel Abidin General Hospital, a referral Hospital in Aceh. Methods: All hospitalized burn injury patient data from January 2016 to December 2017 were collected from the medical record. Data taken included Gender, age, length of stay (LOS), mortality, severity, and extent of the burn, and etiology of burn. Results: From all hospitalized patients with burn injury, the male to female ratio is 1,6:0,9. The mortality rate is 9%, while the others survive. From all etiology of burn, 57% is flame injury, 19% is electrical injury, 18% is scald burn injury, 4% is contact burn injury, and 1% is a chemical burn injury. No patient with first-degree burns was hospitalized, while 13 patients had third-degree burn injuries, and the rest had second-degree burn injuries. Conclusion: An increasing number of hospitalized patients from 2016 to 2017, from 25 patients to 42 patients. It might happen because of increasing knowledge about burn injury in society and physicians in rural areas to refer patients to the hospital with better facilities.